Linear motor. - Aris, Ishak; Iqbal, A. K. M. Parvez (2011)
The present invention relates to a linear motor having improved functionality and design for large displacement. The linear motor comprises of: a stator further comprises of a back yoke and coils for inducing a magnetic field thereby producing flux flowing along air gap to bottom and side of the coils; wherein the coils are winded on a casing , a moving part further comprises of permanent magnets arranged on a shaft, the permanent magnets is positioned at one side of the coil and producing flux flowing in radial direction. The advantageous of the linear motor of the present invention include low noise, reduce operating cost and increased flexibility of operation because of the gearless feature.